(untitled) (Advances in Civil and Architectural Engineering, 2021)
Microsimulation traffic models are used to analyze and predict the functionality and safety of traffic networks, especially in critical areas such as intersections. These models have proven particularly useful in analyzing and comparing solutions in the early stages of design. In this paper, we compare the functional characteristics of an existing two-lane roundabout and a proposed replacement turbo roundabout. Our microsimulation modeling used the VISSIM traffic model, and we designed the conceptual turbo roundabout with AutoCAD and TORUS5 Roundabouts software.